1996
DOI: 10.1002/(sici)1097-4636(199606)31:2<183::aid-jbm4>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metal extract toxicity on human lymphocytes culturedin vitro

Abstract: In this study the toxic effects of chromium, nickel, and cobalt extracts on in vitro cultured lymphocytes were evaluated. Graphite furnace atomic absorption spectrometry was used to measure the ion concentration. After serial dilution of the extracts, the viability of lymphocytes at 24, 48, and 72 h was estimated by flow cytometry, including propidium iodide staining and light scatter property assessment, and by MTT reduction test. The results of the investigation allowed us to conclude that 1) standardization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…7 In vitro tests show that metal ions may be toxic to lymphocytes, and cause cell death or apoptosis. 8,9 In vitro experiments have shown that stainless steel decreases the production of haemopoietic progenitors with detrimental effects being caused by leaching of metal ions. 10 Some haematological alteration, such as a reduction in the number of leukocytes and some subpopulations of lymphocytes, has been observed in patients with aseptic loosening of a THR in which the metal component is worn.…”
mentioning
confidence: 93%
“…7 In vitro tests show that metal ions may be toxic to lymphocytes, and cause cell death or apoptosis. 8,9 In vitro experiments have shown that stainless steel decreases the production of haemopoietic progenitors with detrimental effects being caused by leaching of metal ions. 10 Some haematological alteration, such as a reduction in the number of leukocytes and some subpopulations of lymphocytes, has been observed in patients with aseptic loosening of a THR in which the metal component is worn.…”
mentioning
confidence: 93%
“…A strong decrease in the ATP levels in cells exposed to Cr(VI) was detected in hamster fibroblasts [16,17], human gingival fibroblasts [18][19][20][21], and rat thymocytes [22]. This effect was closely correlated with the inhibition of cellular respiration in human and rat gingival fibroblasts and lymphocytes [16][17][18][19]23], as well as rat thymocytes and hepatocytes [22,24]. The inhibitory action of Cr(VI) on mitochondrial respiration was detected in isolated rat liver [22,24] and heart [25] mitochondria, and also in rat liver submitochondrial particles [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been assigned to the oxidizing activity of Cr(VI), which shunts electrons from electron donors coupled to ATP production, and to the ability of Cr(III), derived from Cr(VI) reduction, to form stable complexes with ATP precursors and enzymes involved in the ATP synthesis [16,17]. Reduction of Cr(VI) has been suggested to occur at the expense of complex I [23,25,26], complex II [19,27], and also complex IV [26] of the mitochondrial electron transport system, interfering with the electron flow [19,23,[25][26][27] and inducing the generation of hydroxyl radicals ( . OH) via the Fenton-mechanism [28].…”
Section: Introductionmentioning
confidence: 99%
“…[52] Results for different types of particles have been reported in the literature, including nanoparticles of titanium dioxide, iron oxide, zinc oxide, and silica [53][54][55] The absorption spectrum of reduced MTT dye is pH dependent, and some metal ions affect the MTT reduction reaction. [56] Hence, nanoparticles could potentially interact with the MTT substrate e.g. by reducing the amount of free MTT and causing a false negative result.…”
Section: Mtt Interference Assaymentioning
confidence: 99%